Looking Toward the Future: Competences for 21st-Century Teacher-Librarians - de Groot, Joanne; Branch, Jennifer L. (Alberta Journal of Educational Research, 2011)
What are the core competences required by teacher-librarians for developing exemplary school library programs in 21st-century schools? This article reports on a study that explored the experiences and attitudes of graduates from the Teacher Librarianship by Distance Learning program at the University of Alberta in Edmonton. Key findings from this study of teacher-librarians indicate that technology and leadership issues are the most pressing needs. These graduates also indicated that their “traditional roles and responsibilities” are changing as they are responsible for promoting new literacies and evaluating, selecting, organizing, and managing diverse learning resources. Quelles sont les compétences de base dont ont besoin les professeurs-bibliothécaires pour développer des programmes de bibliothèque exemplaires pour les écoles du 21e siècle? Cet article décrit une étude qui a exploré les expériences et les attitudes des étudiants diplômés du programme en bibliothéconomie par apprentissage à distance à la University of Alberta à Edmonton. Les principales conclusions découlant de cette étude sur les professeurs-bibliothécaires révèlent que les enjeux relatifs à la technologie et au leadership constituent les besoins les plus immédiats. Les diplômés ont également indiqué que leurs « rôles et responsabilités traditionnels » évoluent puisqu’ils sont responsables de la promotion de nouveaux modes d’alphabétisation, ainsi que de l’évaluation, la sélection, l’organisation et la gestion de diverses ressources d’apprentissage.